Utilization Of Canva Application As A Learning Media For Class Xi History At Man 1 Banjarmasin: Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran Sejarah Kelas XI Di Man 1 Banjarmasin - Muhammad Alian Noor; Herry Porda Nugroho Putro; Heri Susanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The rapid development of technology has brought changes in various sectors of people's lives. One of them is in the education sector. Canva is an online design application, which provides a variety of graphic designs consisting of; presentations, posters, pamphlets, graphics, banners, photo editing and Facebook covers. The purpose of this study is to describe History learning at MAN 1 Banjarmasin, the use of the Canva application as a learning media for History class XI MAN 1 Banjarmasin This study uses a qualitative descriptive method. Data collection techniques use observation, interviews, and documentation. Data sources are taken purposively and snowball. In testing the validity of the data in this study using triangulation techniques. The stages in analyzing data are by reducing data, presenting data and drawing conclusions. The results of the study show that history learning activities using the Canva application by history teachers begin with planning to create lesson plans in accordance with the 2013 curriculum, in the implementation of learning using this Canva application can increase students' creativity in designing to support history learning. The conclusion of the study shows that the application of the Canva application in history learning media by teachers has produced. The use of the Canva application runs effectively and smoothly according to the teacher's instructions. The results show the benefits obtained from the use of the Canva application, the application as a practical learning media increases student creativity, in creating graphic designs. Benefits for teachers help create student projects to create works. Helping teachers to create graphic designs